2022
DOI: 10.1002/ajh.26722
|View full text |Cite
|
Sign up to set email alerts
|

Haploidentical transplantation with post‐transplant cyclophosphamide versus single cord blood transplantation for myelodysplastic syndrome: A retrospective study from the Adult Myelodysplastic Syndrome Working Group of the Japanese Society for Transplantation and Cellular Therapy (JSTCT)

Abstract: Myelodysplastic syndrome (MDS) is a heterogenous group of hematological disorders characterized by dysplastic morphology, peripheral blood cytopenia, and the risk of progression to acute myeloid leukemia (AML). Several therapeutic approaches have been attempted for MDS, including erythroid stimulating agents, immunosuppression, low-dose or intensive chemotherapy, hypomethylating agents, and allogeneic hematopoietic cell transplantation (HCT). Although allogeneic HCT is the only potential curative treatment opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…11,[44][45][46] Our previous study demonstrated comparable survival rates between haploidentical-related donor transplants and CBT in adult patients with MDS. 11 Donor selection might therefore be dependent not only on donor availability, patient and disease circumstances but also on physician and center preference. Third, our findings should be interpreted cautiously when extended to other racial cohorts, because CBT in Japan has several distinctive traits, including the use of single-unit UCB for adults, more flexible selection criteria for UCB units, and a broader indication for advanced disease.…”
Section: Grades Ii-iv Acute Gvhd Grades Iii-iv Acute Gvhdmentioning
confidence: 79%
See 3 more Smart Citations
“…11,[44][45][46] Our previous study demonstrated comparable survival rates between haploidentical-related donor transplants and CBT in adult patients with MDS. 11 Donor selection might therefore be dependent not only on donor availability, patient and disease circumstances but also on physician and center preference. Third, our findings should be interpreted cautiously when extended to other racial cohorts, because CBT in Japan has several distinctive traits, including the use of single-unit UCB for adults, more flexible selection criteria for UCB units, and a broader indication for advanced disease.…”
Section: Grades Ii-iv Acute Gvhd Grades Iii-iv Acute Gvhdmentioning
confidence: 79%
“…Thus, selection bias and the center effect could have affected the results of our study. Second, the use of post‐transplant cyclophosphamide as GVHD prophylaxis has led to a significant increase in haploidentical‐related donor transplants for various hematological diseases, including MDS 11,44–46 . Our previous study demonstrated comparable survival rates between haploidentical‐related donor transplants and CBT in adult patients with MDS 11 .…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The marked increase in the number of UBMT and UCBT in our MSDs. 14 Furthermore, rapid availability is the most important benefit for alternative HLA mismatched donors, such as unrelated cord blood or a haploidentical related donor, 15,16 for MDS patients, because some patients needed an urgent allogeneic HCT (Figure S3B). This ease of donor availability could extend access to allogeneic HCT for MDS because the identification of an MSD can be limited for patients with MDS, particularly in the elderly.…”
mentioning
confidence: 99%